THE HARMONY OF LANGUAGE AND CULTURE: THEORETICAL AND PRACTICAL PERSPECTIVES OF LINGUOCULTUROLOGY (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the interaction between language and culture within the framework of linguoculturology and discourse through a cognitive-pragmatic approach. The main objective of the study is to identify how cultural meanings are constructed and transmitted through linguistic units. The research is based on the theory of linguistic relativity, semiotic approaches, and modern discourse analysis. The findings demonstrate that language functions not only as a means of communication but also as a mechanism for encoding and decoding cultural experience. Furthermore, the study highlights the practical significance of linguoculturology in translation studies, foreign language teaching, and intercultural communication. The results contribute to the development of new theoretical perspectives at the intersection of linguistic and cultural studies.